An empirical evaluation of entrepreneurial orientation in the context of innovation in new ventures. (8th July 2022) - Dinesh, Kamala Kannan; ,
Entrepreneurial orientation as a factor in innovation and entrepreneurship research has gained interest in recent years. This paper attempts to explore and evaluate the dimensions of entrepreneurial orientation in the context of Indian new ventures. Drawing from the existing measurement scale of entrepreneurial orientation, the concept is discussed and addressed in three dimensions: risk-taking ability, innovativeness, and proactiveness. Focusing on strategic innovation in new ventures, this paper also highlights the conceptual relationships among entrepreneurial orientation, organisational innovation, technological innovation, and product innovation. With an aim to understand and assess the dimensions of entrepreneurial orientation in the context of Indian new ventures, the paper presents an empirical evaluation of the concept of entrepreneurial orientation, followed by a discussion of the future research agenda.